2008
DOI: 10.1007/s11858-008-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Building a virtual learning community of problem solvers: example of CASMI community

Abstract: Virtual multidisciplinary learning communities can become an important resource helping school teachers and students to foster a culture of communication, problem solving, and technology integration. Not only does the community concept virtually enlarge the mathematical learning space, it also opens several innovative ways to connect mathematics to other subjects, namely science and language arts. This article reflects on theoretical foundations of the new interactive virtual science and mathematics learning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…One teacher even highlighted the fact that he disliked doing paper-and-pencil marking of students' work, and he hoped that these tools could perform that task. Similar remarks were made by teachers interviewed on our Communauté d'apprentissages multidisciplinaires interactifs (CASMI) project (Freiman & Lirette-Pitre, 2009) who said that because students received individual feedback, it helped them to improve their problem solving skills. However, as shown by LeBlanc and Freiman (2011), this does not mean that this kind of feedback would go beyond pointing at students' mistakes, thus pushing them forward.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…One teacher even highlighted the fact that he disliked doing paper-and-pencil marking of students' work, and he hoped that these tools could perform that task. Similar remarks were made by teachers interviewed on our Communauté d'apprentissages multidisciplinaires interactifs (CASMI) project (Freiman & Lirette-Pitre, 2009) who said that because students received individual feedback, it helped them to improve their problem solving skills. However, as shown by LeBlanc and Freiman (2011), this does not mean that this kind of feedback would go beyond pointing at students' mistakes, thus pushing them forward.…”
Section: Discussionmentioning
confidence: 63%
“…From the pedagogical point of view, teachers expressed the need to use French language videos created by teachers themselves in all disciplines, to help those whose initial training was not in the specific discipline and to facilitate their work during classroom demonstrations. Virtual learning communities already established by researchers (Freiman & Lirette-Pitre, 2009;Jones & Simons, 1999;Pallascio, 2003;Renninger & Shumar, 2002) may have the potential to become professional learning communities. These tools are seen as a palliative element not only in professional practice, but also as a useful element for creation.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the use of this site with over a million hits from more than 100,000 visitors between 2005 and 2010 found that students seemed to appreciate problems that were different from those they encountered in the regular classroom and solving them was more challenging, motivating and enjoyable, even if sometimes problems seemed to be too difficult and frustrating. Personal feedback from mentors was also greatly appreciated (Freiman 2009;Freiman and Lirette-Pitre 2009;Freiman and Manuel 2015).…”
Section: Recreational Mathematicsmentioning
confidence: 99%
“…In a study in Canada, pre-service teachers served as mentors in a context of a virtual mathematics learning community, CASMI (Freiman and Lirette-Pitre 2009) to assess students solving mathematically rich, contextual, and open-ended problems posted on a website that is meant to challenge all children. This activity aimed to help pre-service teachers appreciate the diversity of solutions and learn how to guide schoolchildren in a personalized and caring manner, nurturing their curiosity, interest and perseverance that are very important for all children and especially for the gifted ones.…”
Section: Professional Development Related To Mentoring Students' Onlimentioning
confidence: 99%
“…S. H. Gong [5] think that the construction of a learning community should not paying so much more attention to the hardware as the software is also need to be considered. At the same time, that the formation of the members to the community interaction and the community culture is also very important .To build the effectiveness evaluation index system ,she consider the technology and platform interface, the resources and target orientation, the cultural exchanges and interaction, the emotion and situation atmosphere .Viktor Freiman studied the mathematics and other subjects in the VLC through the new method, and opened up a new way of interaction [6]. Ben Daniel used the hybrid method to find out if the interactive content of students reflects the basic elements of the community [7].…”
Section: Introductionmentioning
confidence: 99%